Assessing How Students Learn in Team-Based Learning: Validation of the Knowledge Re-Consolidation Inventory - Ahn, Hyun Seon (2018)
Purpose: The purpose of the present study was to establish the construct validity of a new instrument to measure psychological learning processes associated with Team-based learning (TBL), the Knowledge Re-Consolidation Inventory (KRCI). The instrument was designed to measure six factors: (1) self-guided preparation, (2) knowledge consolidation, (3) retrieval practice, (4) peer elaboration, (5) feedback, and (6) transfer of knowledge. Method: Two samples were taken, consisting in total of 197 first- and second-year medical students from Singapore. To establish the construct validity of the KRCI, two confirmatory factor analyses were conducted (CFA). First, an exploration sample (N=90) was taken from the second-year medical students to conduct a preliminary CFA, and it resulted in elimination of items with poor psychometric properties. A confirmatory sample (N=107) was then taken from the first-year medical students to conduct a second CFA to cross-validate the KRCI with reduced items. Results: From the original 38 items, 16 remained. The resulting model fitted the data well. The second CFA with the cross-validation sample replicated the findings of the first analysis and supported the factorial structure of the hypothesised six-factor model. Tests of factorial invariance demonstrate that the factorial structure of the KRCI was stable across measurements. Discussion: The results of the study suggest that the KRCI is a valid and reliable instrument capable of measuring the six psychological mechanisms underlying TBL.